Kinematic Analysis of A 4-Axis Manipulator Design with 2-Axis Gripper - Asmara Yanto; Rozi Saferi; Anrinal Anrinal; Fikri Azhar (LP2M - Institut Teknologi Padang, 2019)
The purpose of this work is to analyze the kinematic of a manipulator that was designed to has four revolute movements (R1, R2, R3 and R4) and is equipped with a gripper that has one revolute movement (R) and one prismatic movement (P). The analysis was conducted by varying R1, R2, R3 and R4 of manipulator and R and P of gripper. Kinematic analysis was carried out using the Forward Kinematics method based on DH-Parameters of manipulator and gripper. Manipulator was designed to be consist of 120 mm of Link-1, 200 mm of Link-2, 250 mm of Link-3 and 250 mm of Link-4. Revolute movements range of manipulator was designed for variation of R1, R2, R3 and R4, and with movements range of gripper for variation of R and P. From this work can be concluded that manipulator has 228.5 mm of minimum range radius of end-effector and 547.0 mm of maximum range radius of end-effector.